2023
DOI: 10.1126/sciadv.add6439
|View full text |Cite
|
Sign up to set email alerts
|

Complex carbonaceous matter in Tissint martian meteorites give insights into the diversity of organic geochemistry on Mars

Abstract: We report a huge organic diversity in the Tissint Mars meteorite and the sampling of several mineralogical lithologies, which revealed that the organic molecules were nonuniformly distributed in functionality and abundance. The range of organics in Tissint meteorite were abundant C 3-7 aliphatic branched carboxylic acids and aldehydes, olefins, and polyaromatics with and without heteroatoms in a homologous oxidation structural continuum. Organomagnesium compounds were extremely abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Ryugu’s molecular atlas is characterized by a continuum in oxidized heterocyclic organosulfur and organonitrogen compounds corresponding to a molecular array snapshot of ongoing abiotic reaction processes on the parent body, heavily impacted by water alteration. Abiotic molecular synthesis was described recently in the Martian meteorite Tissint and earlier in ALH 84001 as being the origin of the complex OM observed co-localized to evolving minerals 32 , 33 . Here as well, the chemical signature of the SOM may result from a complex history in carbonization and serpentinization, water-rock interactions generating and consuming water during olivine and pyroxenes dissolution and leaving behind serpentine and an array of oxygenated novel carbon species 34 .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Ryugu’s molecular atlas is characterized by a continuum in oxidized heterocyclic organosulfur and organonitrogen compounds corresponding to a molecular array snapshot of ongoing abiotic reaction processes on the parent body, heavily impacted by water alteration. Abiotic molecular synthesis was described recently in the Martian meteorite Tissint and earlier in ALH 84001 as being the origin of the complex OM observed co-localized to evolving minerals 32 , 33 . Here as well, the chemical signature of the SOM may result from a complex history in carbonization and serpentinization, water-rock interactions generating and consuming water during olivine and pyroxenes dissolution and leaving behind serpentine and an array of oxygenated novel carbon species 34 .…”
Section: Resultsmentioning
confidence: 72%
“…Here as well, the chemical signature of the SOM may result from a complex history in carbonization and serpentinization, water-rock interactions generating and consuming water during olivine and pyroxenes dissolution and leaving behind serpentine and an array of oxygenated novel carbon species 34 . Co-localization of carbon with mineral phases and coevolution within a redox homeostasis will oxidize newly synthesized hydrocarbons while mineral and/or organic electron donors in the mixtures will reduce 32 . These arrays of mixed and localized reactions will create further complex organic molecules in a structural continuum in mass, oxygenation, carbon saturation and heteroatom content.…”
Section: Resultsmentioning
confidence: 99%
“…The SOM content of A0106 is less than that of the CM Murchison and comparable to the SOM contents of the unheated CI Ivuna and Orgueil 4 , 10 , 24 . There is a growing interest in the role of minerals and metals in the co-evolution of organic and inorganic matter 11 , 41 , and the functionality and abundance of organic matter are specific to mineralogical lithologies 8 . Furthermore, a sample of the carbonaceous asteroid (101955) Bennu is scheduled to be returned in 2023 by the OSIRIS-REx mission.…”
Section: Discussionmentioning
confidence: 99%
“…This has provided important insights into the primary chemical profiles and duration of aqueous alteration in the early solar system e.g. 5 8 . The chemical composition of the samples recovered from Ryugu has been found to be most similar to that of the CI group 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The newest fallen martian meteorite, Tissint, has abundant insoluble C-rich materials occurring along the cracks of the host rock or partially transformed into graphite and diamond in the shock-induced veins, indicating that an organic-rich fluid rock interaction could have occurred to facilitate the transportation of organics at the near surface of Mars [ 20 ]. A recent study has shown that Tissint has complex soluble organic matters which are similar to the ones identified in carbonaceous chondrites, indicating that some organics on Mars may have been delivered by asteroid impacts [ 21 ]. Currently, there is no concise conclusion that the organics identified on Mars and in martian meteorites have a biotic and indigenous origin, while the aqueous environment of ancient Mars would be favorable to record the biosignatures of potential life.…”
mentioning
confidence: 99%